A rare case of solitary plasmacytoma mimicking submucosal lesion of ascending colon: a case report and literature review - Carella, Alessandra; Spannella, Francesco; Morè, Sonia; Grifoni, Riccardo; Settanni, Carlo Romano; Mandolesi, Alessandra; Filosa, Alessandra; Goteri, Gaia; Boccoli, Gianfranco; Fava, Giammarco (Frontiers in Oncology, 2024)
Solitary primary extraosseous plasmacytoma is a rare disease in the gastrointestinal tract, recently classified as an "exceptional" tumour of the colon site. The real incidence (1 case/population/year) is unknown, but reasonably less than 1/10.000.000 case/year with very few descriptions in the literature. The rare cases described in the literature are often diagnosed after surgery for perforation and with predominant localization of the left colon. The main endoscopic presentation mimics colon-carcinoma with ulcerated mass and obstructing lumen. In this paper, we report a rare case of isolated mass mimicking submucosal lesion of ascending colon diagnosed in an older female patient by colonoscopy. The patient was almost asymptomatic, she reported only a history of hematochezia without anaemia. This mass was successfully treated by surgery and followed by hematological investigations, including bone marrow biopsy, specific laboratory tests and CT/PET scan, which confirmed primary isolated plasmacytoma of the colon.